Government of the Punjab Property Tax Decentralisation Program : Scope Evaluation Report - World Bank (Washington, DC, 2013)
Property taxation has a long tradition in Pakistan but the Urban Immovable Property Tax (UIPT) provides for only a small amount of revenues because of unclear local government fiscal incentives, an unreliable information base, a low level of motivation, expertise, and insufficient capacity in the UIPT administration. However, the Government of Punjab (GoPunjab) is committed to a fundamental restructuring of the UIPT system. Following a number of World Bank reports a new Punjab Immovable Property Tax Law (PIPT) was drafted in May 2008 and the Bank appointed the Institute of Revenues Rating and Valuation (IRRV) to assess the needs and resources required for, and designing of, a blue print for structural reform and implementation of a property tax decentralization program. The terms of reference require that the Institute shall approach the Punjab property tax system from a broad perspective and take into account the present legal, regulatory, institutional framework, present practices, capacities, circumstances; but build the foundation of the new system in line with the substantial policy reforms contained in the key policy documents adopted by the GoPunjab in 2007-2008.